Bulk properties and 210Pbxs-derived ages for sediment core PS58/270-1 - Struve, Torben; Lamy, Frank; Gäng, Frederik; Klages, Johann Philipp; Kuhn, Gerhard; Esper, Oliver; Lembke-Jene, Lester; Winckler, Gisela (In: Struve, T et al. (2025): Sediment composition and particle flux reconstructions for the Southeast Pacific Antarctic Zone [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982690, 2025)
This dataset contains organic and inorganic bulk sediment properties and 210Pbxs data for core PS58/270-1.
Keywords: glacial-interglacial changes; iron fertilization; particle fluxes; Pleistocene; Southern Ocean; WAIS